2014
DOI: 10.1371/journal.pone.0105366
|View full text |Cite
|
Sign up to set email alerts
|

Use of an In Vivo FTA Assay to Assess the Magnitude, Functional Avidity and Epitope Variant Cross-Reactivity of T Cell Responses Following HIV-1 Recombinant Poxvirus Vaccination

Abstract: Qualitative characteristics of cytotoxic CD8+ T cells (CTLs) are important in measuring the effectiveness of CTLs in controlling HIV-1 infections. Indeed, in recent studies patients who are naturally resistant to HIV-1 infections have been shown to possess CTLs that are of high functional avidity and have a high capacity to recognize HIV epitope variants, when compared to HIV-1 infection progressors. When developing efficacious vaccines, assays that can effectively measure CTL quality specifically in vivo are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…However, the immunodominant CD8 ϩ T cell epitopes of NS5B in BALB/c mice, necessary to synthesize a tetramer in order to detect NS5B-specific CD8 ϩ T cells, are unknown. Consequently, we modified a fluorescent target array (FTA) assay (32)(33)(34) to map the most immunodominant T H and CD8 ϩ T cell epitopes of NS5B in vivo in mice vaccinated with cytolytic DNA encoding NS5B (pVAX-NS5B-PRF). The assay introduces fluorescently labeled bar-coded autologous naive splenocytes pulsed with viral peptides (i.e., the FTA) into previously immunized mice to evaluate the magnitude and/or avidity of T H cell and cytotoxic CD8 ϩ T cell responses in vivo (32)(33)(34).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the immunodominant CD8 ϩ T cell epitopes of NS5B in BALB/c mice, necessary to synthesize a tetramer in order to detect NS5B-specific CD8 ϩ T cells, are unknown. Consequently, we modified a fluorescent target array (FTA) assay (32)(33)(34) to map the most immunodominant T H and CD8 ϩ T cell epitopes of NS5B in vivo in mice vaccinated with cytolytic DNA encoding NS5B (pVAX-NS5B-PRF). The assay introduces fluorescently labeled bar-coded autologous naive splenocytes pulsed with viral peptides (i.e., the FTA) into previously immunized mice to evaluate the magnitude and/or avidity of T H cell and cytotoxic CD8 ϩ T cell responses in vivo (32)(33)(34).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we modified a fluorescent target array (FTA) assay (32)(33)(34) to map the most immunodominant T H and CD8 ϩ T cell epitopes of NS5B in vivo in mice vaccinated with cytolytic DNA encoding NS5B (pVAX-NS5B-PRF). The assay introduces fluorescently labeled bar-coded autologous naive splenocytes pulsed with viral peptides (i.e., the FTA) into previously immunized mice to evaluate the magnitude and/or avidity of T H cell and cytotoxic CD8 ϩ T cell responses in vivo (32)(33)(34). Traditional peptide-based mapping and T cell stimulation assays such as enzyme-linked immunosorbent spot (ELISpot) and intracellular cytokine staining (ICS) analyses do not distinguish CD4 ϩ and CD8 ϩ T cell responses and/or involve prolonged culture/manipulation of T cells in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of live-attenuated or inactivated mucosal vaccines M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 7 should therefore meet the needs for better protection against pathogens that penetrate through mucosal membranes (Neutra & Kozlowski, 2006). Several studies have demonstrated that combined systemic and mucosal prime/ boost immunization can enhance both the humoral and cellular arms of immune responses (Ranasinghe et al, 2006;Srivastava et al, 2008), and different immune outcomes have resulted from combinations of poxvirus vectors using prime/ boost vaccination regimens (Ranasinghe et al, 2006;Wijesundara et al, 2014). Moreover, vaccinations in which DNA priming is followed by a recombinant viral vaccine boost can elicit greater immunity when compared to the use of single immunogens (Lu, 2009;Radaelli et al, 2003;Radaelli et al, 2007;Wang et al, 2008).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%